Impaired neural drive in patients with low back pain. (27th November 2013) - Chiou, S.Y.; Shih, Y.F.; Chou, L.W.; McGregor, A.H.; Strutton, P.H.
Abstract Background Control of trunk movement relies on the integration between central neuronal circuits and peripheral skeletomuscular activities and it can be altered by pain. There is increasing evidence that there are deficits within the central nervous system controlling the trunk muscles in people with low back pain (LBP). However, it is unclear how LBP impacts upon neural drive to back muscles at different levels of voluntary contraction. Therefore, the purpose of this study was to investigate if neural drive is impaired in these patients. Methods Seventeen patients with LBP and 11 healthy controls were recruited. Bilateral electromyographic (EMG) recordings were obtained from the erector spinae (ES) muscles at two vertebral levels (T12 and L4). Participants performed a series of brief isometric back extensions (50–100% maximum voluntary contraction – MVC), during which transcranial magnetic stimulation was delivered. The size of the evoked (superimposed) twitch was measured using dynamometry. Results The size of the superimposed twitch decreased linearly with increasing contraction strength in the controls; however, this linear relationship was not observed in the patients. Additionally, patients had larger superimposed twitches and longer time‐to‐peak amplitudes during MVCs than those observed in controls. Furthermore, patients had lower MVC and root‐mean‐square EMG activity of ES muscles during MVCs. Conclusions A decline of central neural drive to the back muscles at high level of voluntary contraction was observed in patients with LBP. These results suggest that it might be pertinent to include neuromuscular facilitation programmes and therapeutic exercise utilizing high voluntary contractions for patients with LBP.